Functional properties of yacon and atomization by different encapsulating agents (Research, Society and Development, 2021)
The yacon potato is a tuberous root that has been arousing interest, as its composition contains bioactive compounds that offer health benefits. Despite being quite perishable, it has great potential in technology for the development of new food products. The article aims to provide information about yacon, which is considered a functional food, since it has a high content of phenolic compounds, prebiotic and antioxidant characteristics, respectively, and its application of food technology using the atomization process. The microencapsulation process is characterized by the preservation of the original attributes of natural products. Yacon powder from the atomization of the extract, with the use of encapsulating agents such as maltodextrin and gum arabic, is a viable alternative for the preservation of foods with high added value, in addition to contributing to the maintenance of stability and phenolic compounds, even at high temperatures. Therefore, the development of this product represents an important innovation for the food industry.